ANALISIS RASIO PROFITABILITAS DAN NILAI PERUSAHAAN PADA PT ASTRA AGRO LESTARI TBK, PERIODE 2017-2019 - Anggun famela putri; Yospin siang; Ahlul agil akram; Helmi Ramadhan; Marselina dambu; Mursida (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to analyze the profitability ratios and company value of PT Astra Agro Lestari Tbk. This research is a quantitative descriptive using financial ratio analysis in the form of a general description of the company. And the ratios used to measure profitability are Return On Assets (ROA), Return On Equity (ROE) and Net Profit Margin (NPM), while company value is analyzed using Price Book To Value (PBV) which shows that the profitability ratio has decreased and in a bad state. And the value of the company continues to increase and is in good condition.